Do inquiry-based teaching and school climate influence science achievement and critical thinking? Evidence from PISA 2015 (2020)
RESUMEN: : Inquiry-based teaching (IBT) and improving school climate are the two most commonly used strategies for fostering learning and critical thinking skills in students. IBT has positioned itself as one of the most recommended “active” methodologies for developing intellectual autonomy and complex thought processes, whereas school climate is considered to be a protective factor that helps mitigate adverse conditions and has a positive impact on teaching and learning. This study investigates the relationship between IBT and school climate with the academic performance of Colombian students in the PISA 2015 test.